The Broch of Mousa: a Survey by H.M. Office of Works - Paterson, J Wilson (Proceedings of the Society of Antiquaries of Scotland, 1922)
A complete survey of the broch and its outbuildings was carried out while essential repairs took place. It became apparent that there were some errors in the original plans produced in the 19th century. The broch survives to a height of 41 feet. Detailed plans and elevations are presented.